LEARNING WITH COMPUTER SIMULATIONS: A CASE STUDY ON RESERVOIR TEMPERATURES IN CARNOT CYCLES - Velasco, Juan José; Buteler, Laura María; Coleoni, Enrique Andres (Investigações em Ensino de Ciências, 2024)
Computer simulations have played a significant role in the development of physics, and in physics education as well. Researchers have addressed whether simulations promote learning, but few studies have investigated how simulations actually participate in learning processes. This study seeks to describe how simulations participate in conceptual learning. A case study is carried out using videotaped interviews with three groups of undergraduate students as they address a problem-solving task on thermodynamics (Carnot cycles). Students use a specifically developed simulation for support. The analysis is based on Coordination Class Theory (CCT). Results indicate that students not only use the simulation to think; it is actually a part of what they think. Students were found to engage in three different interaction dynamics with the simulation. Attuned with CCT, these were coded as either Extractive/Inferential/Articulative interactions. In each case, the substance of how these interactions input conceptual learning is described. Implications for future research and for teaching are given.